A multispectral microscope for in vivo oximetry of rat dorsal spinal cord vasculature. (18th January 2017) - van der Putten, Marieke A; MacKenzie, Lewis E; Davies, Andrew L; Fernandez-Ramos, Javier; Desai, Roshni A; Smith, Kenneth J; Harvey, Andrew R
Abstract: Quantification of blood oxygen saturation (SO2 ) in vivo is essential for understanding the pathogenesis of diseases in which hypoxia is thought to play a role, including inflammatory disorders such as multiple sclerosis (MS) and rheumatoid arthritis (RA). We describe a low-cost multispectral microscope and oximetry technique for calibration-free absolute oximetry of surgically exposed blood vessels in vivo . We imaged the vasculature of the dorsal spinal cord in healthy rats, and varied inspired oxygen (FiO2 ) in order to evaluate the sensitivity of the imaging system to changes in SO2 . The venous SO2 was calculated as 67.8  ±  10.4% (average  ±  standard deviation), increasing to 83.1  ±  11.6% under hyperoxic conditions (100% FiO2 ) and returning to 67.4  ±  10.9% for a second normoxic period; the venous SO2 was 50.9  ±  15.5% and 29.2  ±  24.6% during subsequent hypoxic states (18% and 15% FiO2 respectively). We discuss the design and performance of our multispectral imaging system, and the future scope for extending this oximetry technique to quantification of hypoxia in inflamed tissue.